Klasifikasi Paket Jaringan Berbasis Analisis Statistik dan Neural Network - Harsono Harsono; Muhammad Khambali; Arif Wirawan Muhammad (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Distributed Denial-of-Service (DDoS) is one of network attack technique which increased every year, especially in both of intensity and volume. DDoS attacks are still one of the world's major Internet threats and become a major problem of cyber-world security. Research in this paper aims to establish a new approach on network packets classification, which can be a basis for framework development on Distributed Denial-of-Service (DDoS) attack detection systems. The proposed approach to solving the problem on network packet classification is by combining statistical data quantification methods with neural network methods. Based on the test, it is found that the average percentage of neural network classification accuracy against network data packet is 92.99%.